Influence of the Bite Natural Angle of Bidentate Diphosphine Ligands in the Syngas-Free Branched Hydroformylation of Beta-Functionalized Olefins - Caroli-Rezende, M; Santander-Meyer, R; Luhr-Sierra, S (ELSEVIER SCIENCE BV, 2018)
The correlation between the activity, regio- and chemoselectivity of Rh-diphosphine catalyst and the ligand bite natural angle (beta(n)) in the syngas-free hydroformylation of allyl cyanide was investigated. A screening of Xantphos type and diphosphine alkyl ligands with different bite natural angles was studied. Interesting, a switch in the linear to the branch regioselectivity was found. Wide beta(n) favour a linear regioselectivity whereas smaller beta(n) allow the formation of the branched aldehyde as the major product. Modification of the substituents at the phosphorus atoms of the diphosphine ligands produced a dramatic change in the hydroformylation. Others beta-functionalized olefins were also branched hydroformylated.